Effect of acupuncture on BDNF signaling pathways in several nervous system diseases - Miao, Chenxin; Li, Xiaoning; Zhang, Yishu (Frontiers in Neurology, 2023)
In recent years, the understanding of the mechanisms of acupuncture in the treatment of neurological disorders has deepened, and considerable progress has been made in basic and clinical research on acupuncture, but the relationship between acupuncture treatment mechanisms and brain-derived neurotrophic factor (BDNF) has not yet been elucidated. A wealth of evidence has shown that acupuncture exhibits a dual regulatory function of activating or inhibiting different BDNF pathways. This review focuses on recent research advances on the effect of acupuncture on BDNF and downstream signaling pathways in several neurological disorders. Firstly, the signaling pathways of BDNF and its function in regulating plasticity are outlined. Furthermore, this review discusses explicitly the regulation of BDNF by acupuncture in several nervous system diseases, including neuropathic pain, Parkinson’s disease, cerebral ischemia, depression, spinal cord injury, and other diseases. The underlying mechanisms of BDNF regulation by acupuncture are also discussed. This review aims to improve the theoretical system of the mechanism of acupuncture action through further elucidation of the mechanism of acupuncture modulation of BDNF in the treatment of neurological diseases and to provide evidence to support the wide application of acupuncture in clinical practice.